Effect of Stad Model of Cooperative Learning on Students’ Learning Outcome on Nomenclature of Hydrocarbon - Nanor, Emmanuel; Mahama, Alhassan; Hanson, Ruby (International Journal of Scientific Research and Management (IJSRM), 2024)
Students Team Achievement Division model of cooperative learning was employed to examine its effect on the learning outcome of students in the concept of nomenclature of hydrocarbons. Forty-one (41) students were purposively sampled for the study. The study employed an action research design. Pre and post-intervention tests were conducted before and after the intervention respectively to determine the effect of the intervention on students’ learning outcome. The findings from the study showed that the STAD model of cooperative learning significantly improved learning outcome of the students in nomenclature of hydrocarbons. The study concluded that STAD model of cooperative learning was an effective learning model for improving students’ learning outcome. The STAD model of cooperative learning provided conducive environment for active participation of learners resulting in meaning construction of knowledge. The intervention provided opportunities for developing analytical and critical thinking skills. The study therefore recommended the use of STAD model of cooperative learning for students owing to its effectiveness in improving learning outcome.